(untitled) (Research, Society and Development, 2022)
Prenatal care has as its main purpose the prevention and early detection of maternal and fetal pathologies, thus, it can provide for the binomial a healthy evolution during the pregnancy and postpartum period, with the objective of promoting health for the population. maternal. Mobile devices have undergone a rapid dissemination among the world population, thus, it was possible to notice the democratization of information about numerous themes, among them, obstetric issues. During the health consultations, the use of software in different formats can be inserted and, as a consequence, the humanization of the pregnancy process could be noticed. This work aims to catalog the current research on the use of software in the assistance of health professionals in prenatal care in Brazil. The works that did not fit the analysis resulted in the removal of 382 works. The exclusion criterion for repetition across platforms removed 448 for the academic community, timeliness is a relevant factor. In addition, it becomes possible to quantify through health indicators to be able to analyze which aspects need to be improved.